EPID-31. EFFICIENT STUDY OF SURGICALLY TREATED MENINGIOMA THROUGH CLINICAL DATA STANDARDIZATION. (11th November 2019) - Au, Karolyn; Nassiri, Farshad; Drummond, Kate; Jenkinson, Michael; Santarius, Thomas; Barnholtz-Sloan, Jill; jungk, Christine; DiMeco, Francesco; Galanis, Evanthia; Saladino, Andrea; Zhou, Yueren; Suppiah, Suganth; et al.
Abstract: With increasing epidemiological and biological studies on meningiomas, standardized clinical data capture will be necessary to interpret results across studies and to translate them to clinical practice. To meet this need for consistent clinical data capture, the International Consortium on Meningioma, has developed a set of common data elements (CDEs), to be used across clinical and biological research. Building from terminology used in clinical practice and ongoing studies, we used a consensus-of-experts approach to arrive at a set of standardized and vetted data elements. Areas of focus include patient characteristics, patient history, radiological and intra-operative description, histological diagnosis and molecular testing, non-surgical interventions, and surveillance. These data elements are implemented in Research Electronic Data Capture (REDCap) forms. With REDCap implementation, components of the CDE set can be selected and instituted in a local REDCap instance for efficient study start-up. The scope of the current CDE set focuses on surgically treated meningioma. However, modular forms provide flexibility and to allow the scope to be expanded to include non-surgically treated meningioma. Dissemination plans are underway to introduce the CDEs to neuro-oncology researchers and clinicians through publication and presentations, where feedback will be solicited. Adoption of CDEs for research will improve consistency and interpretability across studies, expediting research in this frequently occurring tumor.